Analysis of queuing system to improve service quality in the banking sector - Fina Oktafiani; Rahmiati (Operations Management and Information System Studies, 2022)
Queues are one of the problems that are always faced by a bank. The Bank must be able to provide good, fast, and precise service so that customers don’t have to wait too long. Queues occur because the level of customer arrival is greater than the level of service provided. This research was conducted at Bank 9 Jambi Branch of Bangko for five days of observation at 08.00-16.00 IWT. The purpose of this study is to analyze the performance of the queuing system used by Bank 9 Jambi Branch of Bangko and recommend the optimal queuing system for Bank 9 Jambi Bangko Branch. The result of this study indicates that the queuing system used by Bank 9 Jambi Bangko Branch is not optimal and still needs to be improved. After doing the research, the bank must increase the number of tellers from 2 to 3 tellers during peak hours (09.00-11.00 pm) while at non-peak hours it looks optimal with 2 tellers. With the addition of tellers, the target time standard by Bank 9 Jambi Bangko Branch has been met.